Strategi Pengembangan Pariwisata Berkelanjutan di Desa Cihideung Udik Berbasis Lingkungan Pada Fasilitas Penunjang Pariwisata - Sofiani Sofiani; Tatiana Putri Yulia (PolimdoSains, 2023)
The tourism industry should be developed in a sustainable manner based on taking into account environmental sustainability. Cihideung Udik Village is one of the villages located in Bogor Regency which is in the Ciampea sub-district. Cihideung Udik Village has a lot of tourism potential. Starting from the good cultural values ​​of the people, this village also has very beautiful landscapes such as waterfalls, agricultural land and a very beautiful environment and the air is cool. Then the most important thing is that this village is blessed with very abundant water sources. So it's no wonder that in the village of Cihideung Udik there is a water dam which the local people often call the Ciproy Dam, which stands for